Word power : phrasal verbs and compounds : a cognitive approach - Rudzka-Ostyn, Brygida (Mouton de Gruyter, 2003)
Word Power: Phrasal Verbs and Compounds is a textbook for guided self-learning intended for post-intermediate and advanced learners of English. It contains some 1,100 phrasal compounds used with 17 particles/prepositions which combine with some 500 different verbs, nouns and adjectives. Numerous glosses allow the teacher to use it in very heterogeneous classes. Thanks to cognitive linguistics the material is organized around each particle giving the students an astonishing insight into the networks of metaphorical meanings of each particle. Furthermore, the book implements the most important f.
Keywords: English language -- Verb phrase.; English language -- Textbooks for foreign speakers.; Anglais (Langue) -- Syntagme verbal.; Anglais (Langue) -- Manuels pour allophones.; FOREIGN LANGUAGE STUDY -- English as a Second Language.; English language; English language -- Verb phrase; Textbooks -- for foreign speakers